Approaches In Achieving World Class Manufacturing (WCM) In A Semiconductor Manufacturing Plant - Chong, Low Soi (2000)
The semiconductor industry is a dynamic one with seevral hundred companies worldwide fighting for market shae in an ever-expanding international market. The issue of technological leardership aside, companies have to continuosly match higher expectations of customer with shorter lead-times and lower prices. Almost any company can manufacture solutions for the customer, but the differentiation is in price and service. The student has been painfully aware of the company's slide in market share and in area of service.